2021
DOI: 10.1155/2021/7351873
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Bulb Yield of Garlic as Influenced by Clove Size

Abstract: Garlic is an important cash crop in many regions of Ethiopia. However, the yield of the crop is constrained by several factors. Among these, inappropriate clove size is one of the major agronomic practices that can decrease the yield of the crop. Hence, a field experiment was conducted during the 2020/21 main cropping season at Debre Berhan University, College of Agriculture and Natural Resource Sciences, demonstration and research site to evaluate the effect of clove size on growth and bulb yield of garlic (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The VID value had a positive and significant correlation with clove diameter, which means the larger the clove diameter, the higher the VID value. Desta et al (2021) explained that large bulbs germinate faster due to the more excellent supply of carbohydrates in the cloves. The pattern was suited to Chinese softneck garlic.…”
Section: The Role Of the Low Temperature To Break Bulb Dormancy In Ga...mentioning
confidence: 99%
“…The VID value had a positive and significant correlation with clove diameter, which means the larger the clove diameter, the higher the VID value. Desta et al (2021) explained that large bulbs germinate faster due to the more excellent supply of carbohydrates in the cloves. The pattern was suited to Chinese softneck garlic.…”
Section: The Role Of the Low Temperature To Break Bulb Dormancy In Ga...mentioning
confidence: 99%
“…Garlic ( Allium sativum L.) belongs to Alliaceae family, and it is believed to be originated in Central Asia (India, Afghanistan, West China, and Russia) and spread to other parts of the world through trade and colonization and used worldwide as a spice, functional food, and medicinal plant [ 1 ]. Garlic bulbs have a dormancy period of more than three months.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, excessive amounts of water will accelerate rotting process (Oliveira et al, 2020). Desta et al (2021) reported that rainfall amount also influenced the total harvested area or the yield of garlic. The requirements for optimal garlic cultivation are temperatures in range of 20-25°C and annual rainfall of 1,200-2,400 mm (Atif et al, 2020).…”
Section: Introductionmentioning
confidence: 99%